Regional spreading of symptoms at diagnosis as a prognostic marker in amyotrophic lateral sclerosis: a population-based study. Issue 3 (23rd December 2019) - Manera, Umberto; Calvo, Andrea; Daviddi, Margherita; Canosa, Antonio; Vasta, Rosario; Torrieri, Maria Claudia; Grassano, Maurizio; Brunetti, Maura; D'Alfonso, Sandra; Corrado, Lucia; De Marchi, Fabiola; Moglia, Cristina; et al.
Abstract : Objective: The lack of prognostic biomarkers in patients with amyotrophic lateral sclerosis (ALS) induced researchers to develop clinical evaluation tools for stratification and survival prediction. We assessed the correlation between patterns of functional involvement, considered as a cumulative number of body regions involved, and overall survival in a population-based series of patients with ALS (PARALS). Methods: We derived the functional involvement of four body regions at diagnosis using ALSFRS-R subscores for bulbar, upper limbs, lower limbs and respiratory/thoracic regions. We analysed the effect of number of body regions involved (NBRI) at diagnosis on overall survival, adjusting for age at onset, sex, site of onset, diagnostic delay, forced vital capacity, body mass index, mutational status, cognition and comparing it with King's staging system. Results: The NBRI was strongly related to survival, with a progressive increase of death/tracheostomy risk among groups (two body regions HR=1.24, 95% CI 1.06 to 1.45, p=0007; three body regions HR=1.65, 95% CI 1.38 to 1.98, p<0.001; four body regions HR=2.68, 95% CI 2.11 to 3.39, p<0.001). Using ALSFRS-R score, the consistency between the number of regions involved and King's clinical stage at diagnosis was very high (81%). The evaluation of respiratory/thoracic region and cognition allowed to subdivide patients into different prognostic categories. Regional spreading of the disease is associated with survival, independently from the initial region involved. Conclusions: The evaluation of NBRI, with the inclusion of initial respiratory/thoracic involvement and cognition, can be useful in many research fields, improving the stratification of patients. Our findings highlight the importance of the spatial spreading of functional impairment in the prediction of ALS outcome.